Ultrasonic Investigation of Plastically Deformed Steel-Contribution to Analysis of Degradation Influence - Bury, Peter; Barta, S.; Magula, V.; Slugen, V.; Smida, T. (Communications - Scientific letters of the University of Zilina, 2003)
Study of degradation influence on material properties of some steel components is very important because of their serviceable life. One of the most important side of the degradation process considering operation conditions is cumulated plastic deformation. The ultrasonic investigation of materials through the ultrasound attenuation and velocity measurements have been proved an effective tool of the study of structural changes caused also by plastic deformation due to the degradation process. In the contribution we present the results of both the frequency dependence of ultrasound attenuation and velocity measurements of steel samples (38ChN3MFA) with different relative plastic deformation (0, 1.5, 3 and 6 %). The results are compared also with the measurements obtained by some other techniques, including the measurement of electrical conductivity, and the rate of positron-electron annihilation and breakage toughness.